(3ebGdI aj MQcI GdchGcHs
(3ChdgG (B:s
(3jGQGaYkG ddCLQGe GdYdhjI HdG YeO hjG eRjfgG HRjfI GdchGcH CeG HYO aEf UfGYI ESJNQGL GdJbOje hSGFQ GdCYeGd GdeJYdbI s
(3BNQgG (B:s
(3EeG ai HjJ hGMO Ch ai HjJjf aGNQL Pdc GdSge GdhGbY ai GdHjJ HeG YQaJ ChdkG hJee GdYed ceG YQaJ hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs